iTRAQ-Based Proteomic Analysis Reveals the Role of the Biological Control Agent, Sinorhizobium fredii Strain Sneb183, in Enhancing Soybean Resistance Against the Soybean Cyst Nematode - Wang, Yuanyuan; Yang, Ruowei; Feng, Yaxing; Sikandar, Aatika; Zhu, Xiaofeng; Fan, Haiyan; Liu, Xiaoyu; Chen, Lijie; Duan, Yuxi (Frontiers in Plant Science, 2020)
The soybean cyst nematode (SCN), Heterodera glycines Ichinohe, poses a serious threat to soybean production worldwide. Biological control agents have become eco-friendly candidates to control pathogens. Our previous study indicated that the biocontrol agent, Sinorhizobium fredii strain Sneb183, may induce soybean resistance to SCN. To study the mechanisms underlying induced disease resistance in the plant by Sneb183, an iTRAQ (Isobaric tag for relative and absolute quantitation) -based proteomics approach was used to identify proteomic changes in SCN-infected soybean roots derived from seeds coated with the Sneb183 fermentation broth or water. Among a total of 456 identified differentially expressed proteins, 212 and 244 proteins were upregulated and downregulated, respectively, in Sneb183 treated samples in comparison to control samples. Some identified differentially expressed proteins are likely to be involved in the biosynthesis of phenylpropanoid, flavone, flavanol, and isoflavonoid, as well as have a role in disease resistance and adaptation to environmental stresses. We used quantitative real-time PCR (qRT-PCR) to analyze key genes, including GmPAL (phenylalanine ammonia-lyase), GmCHR (Chalcone reductase), GmCHS (Chalcone synthase), and GmIFS (Isoflavone synthase), that are involved in isoflavonoid biosynthesis in Sneb183-treated and control samples. The results showed that these targeted genes have higher expression levels in Sneb183-treated than in control samples. HPLC analysis further showed that the contents of daidzein and genistein in SCN-infected roots of Sneb183-treated samples were 7.24 and 1.62 times higher, respectively than those in infected roots of control samples. These results suggested that Sinorhizobium fredii strain Sneb183 may have a role in inducing isoflavonoid biosynthesis, thereby resulting in enhanced resistance to SCN infection in soybean.